Masquelet Technique for Midfoot Reconstruction Following Osteomyelitis in Charcot Diabetic Neuropathy: A Case Report. Issue 2 (April 2015) - Mak, May Fong; Stern, Richard; Assal, Mathieu
Abstract : Case: We describe a case of ulcerative midfoot osteomyelitis in a patient with Charcot diabetic neuropathy. After debridement, an extensive osseous defect led to staged reconstruction in an attempt to salvage the foot. We describe the presentation, the treatment, and the technical points of this challenging case. Conclusion: We reconstructed the midfoot defect with use of the induced-membrane Masquelet technique, successfully reestablishing a stable, well-aligned, plantigrade, ulcer-free foot.